Filamentous fungi of medical importance in drinking water - Leal, André Ferraz Goiana (2010)
This study aimed to assess the occurrence of fungi in water sample, tap and sink from drinking fountains at the university center, Recife-PE, Brazil. From each fountain, 100mL of water were collected, and the samples from the tap and sink surfaces were obtained by using swabs. The samples were cultivated on Sabouraud agar medium containing 50mg/L of chloramphenicol in Petri dishes. Of water samples, 10 isolates of filamentous fungi were found and identified as Aspergillus flavus (5), A. niger (3) and Cladosporium cladosporioides (2). Twenty-one strains of filamentous fungi were isolated from tap samples and 164 from sink samples. The number of colony forming units (CFU) (48h) ranged from 12 to 56 in water samples, from 115 to 228 in samples collected from taps, and 204 to 690 in sink samples. Fungi capable of producing mycotoxins were detected in both water and taps samples. Monitoring the microbial and chemical quality of water and the maintenance of water purification equipment are crucial to guarantee the consumers safety.